In Search of the Perfect Filter: Indexing Theory Implications for Internet Blocking and Rating Software Products - Schrader, Alvin M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Growing public concern about controversial content on the Internet has inspired a political and technological challenge to open access. The political challenge is represented in a myriad of coercive legislative initiatives by politicians and government actors across the globe to control the technology of access to the Internet The technological challenge takes the form of an increasing array of . . .